Pengaruh Sistem Monitoring Pengisian dan Konsumsi Daya pada Pembangkit Listrik Tenaga Hybrid (Surya Dan Bayu) Berbasis Platform Thingspeak - Asmida, Asmida; Yurika, Yurika (Universitas Pahlawan Tuanku Tambusai, 2024)
The increasing human population and life dependent on energy causes the planet to lack energy, especially fossil fuels. Renewable energy is energy that comes from a continuous natural process and never runs out, along with the development of the era, new innovations have emerged, especially in renewable energy sources such as hybrid power plants. To determine the effectiveness and suitability of parameters in a Hybrid Power Plant, it is necessary to be equipped with an effective control system and can be monitored from close up or from a distance, therefore a monitoring system based on the internet of things is needed. The results of the tests carried out were charging energy to the battery, the calculated value of the PLTS voltage was 18 V, the battery voltage was 13.01 V while the current produced was 1.05 A. The PZEM004T sensor was simulated with a load of two soldering irons, it was known that the sensor detected a voltage of 226.6 V, a current of 0.26 V, and a power of 59.00 V, the data was sent to the thingspeak platform in 10 seconds.